ANALISIS HUKUM TENTANG PENERAPAN UNDANG-UNDANG NOMOR 7 TAHUN 2017 MENGENAI TINDAK PIDANA DALAM PROSES PEMILIHAN UMUM - Rizki, Fikri; Amsori, Amsori (Journal Evidence Of Law, 2023)
Indonesia is a country that adheres to democratic principles in its system of government. Indonesia has three institutions that are responsible for ensuring the implementation of democratic elections run well. This study is entitled legal analysis of the application of Law No. 7 of 2017 concerning criminal acts in the general election process. With the formulation of the problem, namely how the role of integrated law enforcement centers in election law enforcement and how law enforcement against election crimes based on Law Number 7 of 2017. Using normative juridical legal methods. Conclusion: Indonesia is a country that adheres to democratic principles in its system of government. Indonesia” has three institutions that are responsible for ensuring the implementation of democratic elections run well.